Centrosymmetric Binuclear Boron Compounds Derived from Dithiooxamides: Synthesis, Characterization, and Their Photophysical Properties - Marisol Ibarra-Rodríguez; Blanca M. Muñoz-Flores; Jesús Lara Cerón; Rosa Santillán; María E. Ochoa; Noemí Waksman; Víctor M. Jiménez-Pérez (Journal of Chemistry)
In this paper, we report the synthesis and characterization of new boron compounds derived from dithiooxamides. The compounds were characterized by NMR (1H and 13C), UV-vis, fluorescence spectroscopy, and high resolution mass spectrometry. The crystal structure of the mononuclear boron compound was determined by single-crystal X-ray diffraction analysis. The photophysical properties of the boron compounds were investigated, and we found moderate fluorescence emission (compound 2 ΦF: 4.07% and compound 4 ΦF: 2.89%). We also observed that the mononuclear complex presented greater stability. Compound 4 showed interesting luminescent properties; in solid state, it exhibited an increase in fluorescence by mechanostimuli by changing to a bright red color, and also in solution, it showed a decrease in fluorescence intensity when oxygen and air were supplied to the solution.